An Analysis of the Meaning of the Word Auliyā’ in the 2019 Edition of the Indonesian Ministry of Religious Affairs' Qur’anic Translation: A Critical Discourse Perspective - Ahmad Fajri; Nur Rofiah; Azmi Ismail (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
The translation of key Qur’anic terms plays a crucial role in shaping public religious understanding, particularly in multicultural societies like Indonesia. One such term is auliyā’, whose interpretation can carry significant theological and sociopolitical implications. This study analyzes the translation of auliyā’ in the 2019 edition of the Qur’an published by the Indonesian Ministry of Religious Affairs, aiming to identify shifts in its meaning and explore how these reflect national and social values. Employing a qualitative method within the framework of Critical Discourse Analysis (CDA), the research draws on Teun A. van Dijk’s model, integrating literature review, textual analysis, and interviews with translators and policymakers. The findings indicate that the term auliyā’ is rendered as "faithful friends," which narrows its meaning from the broader classical interpretations such as "allies," "leaders," or "guardians." This choice appears to be a deliberate domestication strategy aimed at fostering interreligious harmony and minimizing sectarian tension. It aligns with Indonesia’s Pancasila values, emphasizing unity, tolerance, and pluralism. The study concludes that translation is not merely a linguistic act but also a socio-political engagement that can reinforce national ideology. This research contributes to the field of Qur’anic translation studies by highlighting the role of localized interpretations in promoting inclusive religious discourse within diverse national contexts.